2022
DOI: 10.1177/11772719221091758
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of rs12702634 in RPA3-UMAD1 With Interstitial Lung Diseases in Japanese Rheumatoid Arthritis Patients

Abstract: Background: Rheumatoid arthritis (RA) is occasionally complicated with interstitial lung disease (ILD). A recent genome-wide association study of ILD in RA reported an association with the polymorphism rs12702634 in RPA3-UMAD1. We conducted an association study of this variant with ILD in Japanese RA patients to replicate this association. Methods: Genotyping of rs12702634 was performed in 175 RA with ILD and 411 RA without chronic lung disease. Results: No association was detected for rs12702634 with ILD in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
1
2
Order By: Relevance
“…Other genetic factors were suspected to be associated with ILD in Japanese RA. RPA3-UMAD1 rs12702634 was reported to be associated with ILD in the GWAS of Japanese RA, 9 but the association described in that study was not confirmed in our replication study in other Japanese populations, 10 suggesting heterogeneity of ILD in RA. The confirmation of the results of genetic association studies by replication is important to establish their validity.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Other genetic factors were suspected to be associated with ILD in Japanese RA. RPA3-UMAD1 rs12702634 was reported to be associated with ILD in the GWAS of Japanese RA, 9 but the association described in that study was not confirmed in our replication study in other Japanese populations, 10 suggesting heterogeneity of ILD in RA. The confirmation of the results of genetic association studies by replication is important to establish their validity.…”
Section: Discussioncontrasting
confidence: 75%
“…RPA3-UMAD1 rs12702634 was reported to be associated with ILD in Japanese RA in a genome-wide association study (GWAS) 9 but was not confirmed in our replication study in other Japanese populations. 10 Another recent GWAS revealed that SNVs in MUC5B , TOLLIP , FAM13A and TERT genes were associated with ILD in European RA. 11 In addition to MUC5B , an association of FAM13A with idiopathic pulmonary fibrosis has been reported in GWAS or candidate gene studies.…”
Section: Introductionmentioning
confidence: 99%
“…The risk allele of the SNV upregulates mucin 5B expression and might interfere alveolar repair. In a study by another group, an SNV in RPA3-UMAD1 was also associated with RA-associated interstitial lung disease [13], but this was not confirmed in our replication study [14]. Associations of TOLLIP, MUC5B, TERT, and FAM13A SNVs with interstitial lung disease were reported in RA patients from European populations [15].…”
Section: Introductioncontrasting
confidence: 68%